CuO-TiO2 as a visible light responsive photocatalyst for the photoelectroreduction of CO2 to methanol - Karim, Kaykobad Md. Rezaul; Mariotte, Patrick Jebi; Huei, Ruey Ong; Hamidah, Abdullah; Tarek, Mostafa; Cheng, C. K.; Khan, Maksudur R. (Universiti Malaysia Pahang, 2018)
As rising atmospheric CO2 levels change Earth’s climate change, CO2 reduction has become an increasingly active area in energy research over the past several years. The present work is developing artificial photosynthesis technologies that use visible light to convert CO2 and water into methanol. In this study, TiO2 loaded copper oxide (CuO-TiO2) was synthesized, characterized and studied for photoelectrochemical (PEC) reduction of CO2 into methanol under visible light (λ > 470 nm) irradiation. In this perspective, the catalyst was synthesized via Sol-gel method. Catalyst characterization was done by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), UV-vis absorption spectra, and Mott-Schottky (MS). Linear sweep voltammetry (LSV) was employed to evaluate the photocatalytic activity of the prepared photocatalyst under visible light (λ >420 nm) irradiation for CO2 reduction reactions. XRD results indicated that the particle size of the as-prepared photocatalyst was 65 nm. The oxidation state of Cu2+ and Ti4+ were confirmed by XPS results. The band gap of CuO-TiO2 composite characterization results indicated that the band gap energy of the CuO-TiO2 catalyst was 1.68 eV. The flat band potential was calculated from the MS data and was found at 0.83 V vs NHE. During LSV, the onset potential was shifted positively (~100 mV) under the light on condition than the dark condition in CO2 saturated solution suggests an increase in photocurrent and occurrence CO2 photoreduction reaction. The PEC performance of CuO-TiO2 photocatalyst showed an increased methanol formation and found the optimum yield of 20.1 μmol.L-1cm-2 under visible light irradiation.